Foul Ball: Audience-Held Stereotypes of Baseball Players. Issue 1 (2nd January 2016) - Ferrucci, Patrick; Tandoc, Jr., Edson C.; E. Painter, Chad; Wolfgang, J. David
Abstract: This study experimentally tested whether participants held and/or applied stereotypes of baseball players. Participants were asked to rate White, Black, and Latino baseball players based on stereotypes consistently identified in previous literature. Participants saw a photo of a player and an anonymous paragraph from a newspaper that highlighted a particular stereotype. They were then asked to rate the author's credibility. Black players were rated as higher in physical strength and natural ability, consistent with previous literature concerning how athletes were described. However, White and Latin players were not stereotyped. But participants rated White-consistent descriptions as credible and Latin-consistent descriptions as less credible. These results are interpreted through the prism of social identity theory.